'Investing in Farmers--The Impacts of Farmer Field Schools in Relation to Integrated Pest Management'--A Comment - Feder, G.; Murgai, R.; Quizon, J. (2012)
In a recent article in World Development, van den Berg and Jiggins [van den Berg, H. and Jiggins, J. (2007). Investing in farmers: The impacts of farmer field schools in relation to integrated pest management. World Development, 35(4), 663-686] (to be referred to in the discussion below as the "BJ paper") challenge the validity of results in two papers written by us, [Feder, G., Murgai, R., and Quizon, J. (2004a). Sending farmers back to school: the impact of farmer field schools in Indonesia, Review of Agricultural Economics 26(1), 45-62, Feder, G., Murgai, R. and Quizon, J. (2004b). The acquisition and diffusion of knowledge: the case of pest management training in farmer field schools, Indonesia. Journal of Agricultural Economics 55(2), 217-239] focusing their criticism on a number of points, and concluding that our studies "appear to be less authoritative than they purport to be." In the following, we will discuss the various points raised in the BJ paper, and show that they do not amount to a significant challenge to the validity of our results.